قضايا الزواج والطلاق عند مسلمي سريلانكا : مشروع مقترح للحكومة - محي الدين، نعيم محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
Dramatic changes in Sri Lankan Muslims' life have resulted due to many reasons such as mixing with non-Muslims, the advancement in technology and applied sciences. Consequently, the problems and issues related to human life have turned out to be multiple and complex in nature. Although constantly arising problems have been dealt with by scholars, other issues remain to be examined. One such issue that necessitates a study is the Muslim family laws of Sri Lanka in the light of Islamic jurisprudence. In this regard, this study aims at examining the current problems and issues related to marriage and divorce among the Muslim minority of Sri Lanka. For this purpose, this research employs several methods including the inductive approach in dealing with the statements and opinions of Islamic scholars in family law, the deductive method to analyze the texts of jurisprudence and the historical approach to track the origin of the Muslim personal law for muslims of Sri Lanka, its development and the reasons that lead to the occurence of errors. In conclusion, this study highlights specific issues as urgent needs to amended: the bad tradition of dowry (Kaikooli) needs to be questioned and consequently abolished; marriage to Jewish and Christian women should be prohibited thus blocking the means to an evil (saddan liddara'i), when a Muslim is in the need to raise an issue to a non-Muslim judge, his judgment will be implemented so as not to disrupt the interests of Muslims, and for people who enter Islam in order to marry, just stating the statement of faith (shahaadatain) is not sufficient, but their truthfulness to Islam, commitment to Islamic rituals, loyalty to Allah, his Messenger and the believers, and other fundamentals of Islam, should also be verified. Other crucial matters are also discussed. Taking these issue into consideration, the study finally suggests amendments and modern ijtihad (re-ijtihad) in the Muslim personal law in Sri Lanka.